Ternary heterostructure CoFe2O4 / ZnO-RGO nano composite electromagnetic wave absorbing material as well as preparation method and application thereof

By combining CoFe2O4, ZnO nanorods with RGO, a heterostructure of a three-dimensional conductive network is constructed, which solves the problem that existing electromagnetic wave absorbing materials cannot simultaneously meet the requirements of thinness, lightness, width, and strength, and achieves excellent wave absorption performance at various thicknesses and environmentally friendly production.

CN121376994APending Publication Date: 2026-01-23CHANGZHOU TONGFENG PAINT +1

Patent Information

Application Number
CN202511738568.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-25
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

Existing electromagnetic wave absorbing materials cannot simultaneously meet the requirements of being thin, light, wide, and strong, and their preparation process is complex or not environmentally friendly.

Method used

By combining magnetically depleted CoFe2O4, dielectrically depleted ZnO nanorods with resistively depleted RGO, a heterostructure of a three-dimensional conductive network is constructed, optimizing impedance matching and electromagnetic attenuation capabilities.

Benefits of technology

It achieves excellent wave absorption performance at various thicknesses, especially under ultra-thin conditions. The material is widely available, inexpensive, and suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121376994A_ABST
    Figure CN121376994A_ABST
Patent Text Reader

Abstract

The invention discloses an electromagnetic wave absorbing material CoFe2O4 / ZnO-RGO with a ternary heterostructure as well as a preparation method and application of the electromagnetic wave absorbing material CoFe2O4 / ZnO-RGO, and belongs to the technical field of electromagnetic wave absorption. According to the material, a novel heterostructure with a multi-scale interface and a three-dimensional conductive network is constructed by compounding magnetic loss type CoFe2O4, dielectric loss type ZnO nanorods and resistance loss type RGO. Wherein the ZnO nanorod not only serves as a dielectric loss body, but also effectively enhances the structural anisotropy and the interface polarization effect of the material, and cooperates with the magnetic loss of CoFe2O4 and the resistance loss of RGO to jointly optimize impedance matching and improve the electromagnetic attenuation capability, so that the material shows excellent wave-absorbing performance under various thickness and even ultrathin conditions. The material source is wide, the cost is low, the preparation process is green, simple and convenient, the material is suitable for large-scale production, and an effective material solution is provided for electromagnetic wave absorption application in the national defense and civil fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electromagnetic wave absorption, specifically, it relates to a ternary heterostructure CoFe2O4 / ZnO-RGO nanocomposite electromagnetic wave absorbing material and its preparation method. Background Technology

[0002] With the rapid development of electronic information technology and the widespread application of wireless communication equipment, electromagnetic waves, while bringing convenience to human life, have also brought increasingly serious electromagnetic pollution and interference problems. Therefore, developing high-performance electromagnetic wave absorbing materials to achieve efficient absorption and shielding of electromagnetic waves has become an important research direction in the field of functional materials. An ideal electromagnetic wave absorbing material should possess characteristics such as thinness, low density, high absorption intensity, wide absorption bandwidth, and good environmental stability, and should be able to meet the needs of practical engineering applications.

[0003] Among numerous microwave absorbing materials, carbon-based materials, especially graphene, are widely considered an ideal matrix material due to their high specific surface area, excellent conductivity, and lightweight properties. For example, Chinese patent 202510046616.0 uses aniline compounds and graphene as raw materials to prepare composite materials through group grafting technology. The prepared material achieves a minimum reflection loss of -51.17 dB at 10.24 GHz and an effective bandwidth of 4.84 GHz. However, the existing technology of combining graphene with toxic aniline compounds is not conducive to environmental protection and the process is complex. Furthermore, combining magnetic materials with graphene has made it highly favored in the field of microwave absorbing materials, as it can combine magnetic loss and dielectric loss mechanisms to improve microwave absorption performance. For example, Chinese patent 202510343260.7 uses ultrafine spherical carbon-based iron powder and flake graphite as raw materials and employs dry ball milling technology to prepare microwave absorbing composite materials. This material shows certain absorption potential; however, the magnetic components often have high density and poor chemical stability, and are prone to oxidation or agglomeration, which limits its practical application. Therefore, constructing a new type of green and environmentally friendly composite material that combines lightweight, strong absorption, wide bandwidth, and good stability is of urgent research significance and application value. Summary of the Invention

[0004] Simple resistive loss, dielectric loss, or magnetic loss type absorbing materials cannot meet the requirements of "thin, light, wide, and strong" for new absorbing materials. Therefore, it is urgent to develop a simple and quick method to prepare composite absorbing materials with multiple electromagnetic wave loss mechanisms, and the process should be low-carbon, environmentally friendly, and easy to mass-produce.

[0005] To effectively address these issues, this invention creatively proposes a novel high-efficiency microwave absorption material prepared by combining magnetic loss-type materials (cobalt ferrite), dielectric loss-type materials (zinc oxide), and resistive loss-type materials (reduced graphene oxide). The materials used in this invention are widely available and inexpensive, and the preparation process is green, simple, and easy to implement, making it suitable for large-scale production. This invention provides a theoretical method and preparation route for electromagnetic wave absorption applications in national defense and civilian fields.

[0006] To address the aforementioned technical problems, the present invention adopts the following technical solution: This invention constructs a novel heterostructure with multi-scale interfaces and a three-dimensional conductive network by compositing magnetically depleted CoFe₂O₄, dielectrically depleted ZnO nanorods, and resistively depleted Resonant Organic Gas (RGO). The ZnO nanorods not only act as dielectric loss conductors themselves but also effectively enhance the material's structural anisotropy and interfacial polarization effects. Together with the magnetic loss of CoFe₂O₄ and the resistive loss of RGO, they optimize impedance matching and improve electromagnetic attenuation capabilities, resulting in superior microwave absorption performance across various thicknesses, even ultrathin conditions. The materials in this invention are widely available, inexpensive, and employ a simple and environmentally friendly manufacturing process, making them suitable for large-scale production. This provides an effective material solution for electromagnetic wave absorption applications in both defense and civilian sectors.

[0007] The purpose of this invention is to provide a ternary heterostructure CoFe2O4 / ZnO-RGO nanocomposite electromagnetic wave absorbing material, wherein the absorbing material comprises CoFe2O4, ZnO and reduced graphene oxide (RGO), and spherical CoFe2O4 nanoparticles and ZnO nanorods together constitute a heterostructure, which is loaded on the surface of sheet-like reduced graphene oxide.

[0008] Further specifying, the reduced graphene oxide is a single-layered, wrinkled structure.

[0009] Further specifying, the mass percentages of the CoFe2O4 nanoparticles, ZnO, and RGO are 8.9%~22.4%, 74.6%~89.3%, and 1.7%~3.3%, respectively.

[0010] Another objective of this invention is to provide a method for preparing the above-mentioned ternary heterostructure CoFe2O4 / ZnO-RGO nanocomposite electromagnetic wave absorbing material.

[0011] A method for preparing a ternary heterostructured CoFe2O4 / ZnO-RGO nanocomposite electromagnetic wave absorbing material includes the following steps: Step 1: Disperse reduced graphene oxide in ethylene glycol to obtain an RGO solution, then add sodium hydroxide, sonicate until completely dissolved, add zinc acetate, and stir until homogeneous to obtain a suspension; Step 2: Then add spherical CoFe2O4 nanoparticles, sonicate, heat to react, cool after the reaction is complete, wash repeatedly with deionized water and anhydrous ethanol, centrifuge, and dry to constant weight to obtain the absorbent material.

[0012] Further specifying the preparation method of RGO, it is as follows: 140 mg of graphite oxide (GO) and 140 mg of sodium dodecylbenzenesulfonate (SDBS) are dispersed in 140 mL of deionized water, 0.5 mL of 80 wt% hydrazine hydrate is added, and the reaction is carried out in a water bath at 80 °C for 24 h. After the reaction is completed, the product is collected and washed by vacuum filtration.

[0013] Further specified, CoFe2O4 nanoparticles were prepared by the following method: 1.35 g FeCl3·6H2O and 0.7 g CoCl2·6H2O were added to 40 mL of ethylene glycol, and after ultrasonic dispersion and uniform mixing, 1.8 g sodium acetate and 0.5 g polyethylene glycol were added and ultrasonically dissolved again. After stirring at 50 ℃ for 1 h, the mixture was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 200 ℃ for 8 h. After cooling to room temperature, the mixture was separated by magnetic precipitation, washed with deionized water and anhydrous ethanol, and dried to obtain CoFe2O4 nanoparticles.

[0014] Further specified, the mass ratio of NaOH to RGO solution volume is (1.0~2.0) g : (20~40) mL, the concentration of RGO solution is 1.0 mg / mL, and the mass ratio of NaOH to zinc acetate is (1.0~2.0) : (0.5~1.5).

[0015] Further specifying, the mass ratio of NaOH to spherical CoFe2O4 nanoparticles is (1.0~2.0):(0.5~1.5).

[0016] Further specified, the reaction is carried out at a heating temperature of 120 ℃ to 180 ℃.

[0017] Furthermore, the use of the ternary heterostructure CoFe2O4 / ZnO-RGO nanocomposite electromagnetic wave absorbing material of the present invention is also provided, for electromagnetic wave absorption.

[0018] The product CoFe2O4 / ZnO-RGO was ground and mixed with paraffin to form a coaxial ring. Its electromagnetic parameters were measured in a vector network analyzer. The reflection loss value was calculated by substituting into formulas (1) and (2) to evaluate the wave absorption performance of the composite material.

[0019] (1) (2) Compared with the prior art, the present invention has the following beneficial effects: The raw materials used in this invention are widely available, the preparation cost is low, and the reaction process is green, simple, and easy to implement, making it suitable for large-scale production.

[0020] This invention creatively combines magnetic loss type, dielectric loss type and resistive loss type materials to form a ternary heterostructure. Through the synergistic effect of multiple interface polarizations and dipole polarizations as well as conduction losses, it achieves optimal impedance matching and excellent attenuation characteristics, exhibiting excellent electromagnetic wave absorption performance at various thicknesses and even ultrathin thicknesses.

[0021] For a deeper understanding of the features and technical content of this invention, please refer to the accompanying detailed description and drawings. It should be noted that the drawings are provided for illustrative purposes only and are not intended to limit the scope of the invention. Attached Figure Description

[0022] Figure 1 This is a transmission electron microscope image of the CoFe2O4 / ZnO-RGO prepared in Example 3; Figure 2 The X-ray diffraction pattern of CoFe2O4 / ZnO-RGO prepared in Example 3; Figure 3 The graph shows the relationship between the complex permittivity and frequency of CoFe2O4 / ZnO-RGO prepared in Example 3 in the range of 2~18 GHz; Figure 4 The graph shows the relationship between the complex permeability and frequency of the CoFe2O4 / ZnO-RGO prepared in Example 3 in the range of 2~18 GHz; Figure 5 The graph shows the relationship between the loss tangent and frequency of the CoFe2O4 / ZnO-RGO prepared in Example 3 in the range of 2~18 GHz; Figure 6 The image shows the 3D reflection loss of CoFe2O4 / ZnO-RGO prepared in Example 3. Figure 7 The image shows the frequency-dependent reflection loss curves of the CoFe2O4 / ZnO-RGO prepared in Example 3 at different thicknesses. Detailed Implementation

[0023] The present invention will be described in detail below with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but should not be considered as limiting the present invention. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0024] The ethylene glycol solution containing RGO used below was prepared by the following method: using a redox method, 140 mg of graphene oxide and 140 mg of sodium dodecylbenzenesulfonate were dispersed in 140 mL of deionized water, and 0.5 mL of 80 wt% hydrazine hydrate was added. The reaction was carried out in a water bath at 80 °C for 24 h. After the reaction was completed, the graphene was collected and washed by vacuum filtration, and finally dispersed in ethylene glycol to obtain an ethylene glycol solution of RGO with a concentration of 1.0 mg / mL.

[0025] The CoFe2O4 nanoparticles used below were prepared by the following method: 1.35 g FeCl3·6H2O and 0.7 g CoCl2·6H2O were added to 40 mL of ethylene glycol, and after ultrasonic dispersion and uniform mixing, 1.8 g sodium acetate and 0.5 g polyethylene glycol were added and ultrasonically dissolved again. The mixture was then transferred to a round-bottom flask, stirred at 50 °C for 1 h, and then transferred to a 100 mL polytetrafluoroethylene reactor. The reaction was carried out at 200 °C for 8 h. After cooling to room temperature, the mixture was separated by magnetic precipitation, washed three times with deionized water and anhydrous ethanol, and dried to obtain CoFe2O4 nanoparticles.

[0026] Example 1: A method for preparing a ternary heterostructure electromagnetic wave absorbing material CoFe2O4 / ZnO-RGO is carried out according to the following steps: 1.0 g of sodium hydroxide (NaOH) was dissolved in 20 mL of ethylene glycol solution with a concentration of 1.0 mg / mL RGO. The solution was ultrasonically treated for 1 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Then, 0.5 g of zinc acetate (C4H6O4Zn·2H2O) was added to the solution and stirred for 0.5 h to form a suspension. Subsequently, 0.1 g of nano-CoFe2O4 particles were added and dispersed in the suspension. The solution was ultrasonically treated for 0.5 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Finally, the mixture was transferred to a polytetrafluoroethylene reactor and reacted at 120 °C for 18 h. After the reaction was completed, the mixture was cooled and washed multiple times with deionized water and anhydrous ethanol. The mixture was collected by centrifugation and finally dried to obtain the CoFe2O4 / ZnO-RGO composite material.

[0027] Example 2: The preparation of a ternary heterostructure electromagnetic wave absorbing material CoFe2O4 / ZnO-RGO was carried out according to the following steps: 1.5 g of sodium hydroxide (NaOH) was dissolved in 30 mL of ethylene glycol solution with a concentration of 1.0 mg / mL RGO. The solution was ultrasonically treated for 1 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Then, 1.5 g of zinc acetate (C4H6O4Zn·2H2O) was added to the solution and stirred for 1 h to form a suspension. Subsequently, 0.15 g of nano-CoFe2O4 particles were added and dispersed in the suspension. The solution was ultrasonically treated for 0.5 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Finally, the mixture was transferred to a polytetrafluoroethylene reactor and reacted at 160 °C for 20 h. After the reaction was completed, the mixture was cooled and washed multiple times with deionized water and anhydrous ethanol. The mixture was collected by centrifugation and finally dried to obtain the CoFe2O4 / ZnO-RGO composite material.

[0028] Example 3: The preparation of a ternary heterostructure electromagnetic wave absorbing material CoFe2O4 / ZnO-RGO was carried out according to the following steps: 1.5 g of sodium hydroxide (NaOH) was dissolved in 40 mL of ethylene glycol solution with a concentration of 1.0 mg / mL RGO. The solution was ultrasonically treated for 1 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Then, 1.0 g of zinc acetate (C4H6O4Zn·2H2O) was added to the solution and stirred for 1 h to form a suspension. Subsequently, 0.2 g of nano-CoFe2O4 particles were added and dispersed in the suspension. The solution was ultrasonically treated for 0.5 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Finally, the mixture was transferred to a polytetrafluoroethylene reactor and reacted at 180 °C for 22 h. After the reaction was completed, the mixture was cooled and washed multiple times with deionized water and anhydrous ethanol. The mixture was collected by centrifugation and finally dried to obtain the CoFe2O4 / ZnO-RGO composite material.

[0029] Example 4: The preparation of a ternary heterostructure electromagnetic wave absorbing material CoFe2O4 / ZnO-RGO was carried out according to the following steps: 1.0 g of sodium hydroxide (NaOH) was dissolved in 20 mL of ethylene glycol solution with a concentration of 1.0 mg / mL RGO. The solution was ultrasonically treated for 1 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Then, 0.5 g of zinc acetate (C4H6O4Zn·2H2O) was added to the solution and stirred for 1 h to form a suspension. Subsequently, 0.15 g of nano-CoFe2O4 particles were added and dispersed in the suspension. The solution was ultrasonically treated for 0.5 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Finally, the mixture was transferred to a polytetrafluoroethylene reactor and reacted at 160 °C for 20 h. After the reaction was completed, the mixture was cooled and washed multiple times with deionized water and anhydrous ethanol. The mixture was collected by centrifugation and finally dried to obtain the CoFe2O4 / ZnO-RGO composite material.

[0030] Example 5: The preparation of a ternary heterostructure electromagnetic wave absorbing material CoFe2O4 / ZnO-RGO was carried out according to the following steps: 1.5 g of sodium hydroxide (NaOH) was dissolved in 30 mL of ethylene glycol solution with a concentration of 1.0 mg / mL RGO. The solution was ultrasonically treated for 1 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Then, 1.5 g of zinc acetate (C4H6O4Zn·2H2O) was added to the solution and stirred for 1 h to form a suspension. Subsequently, 0.2 g of nano-CoFe2O4 particles were added and dispersed in the suspension. The solution was ultrasonically treated for 0.5 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Finally, the mixture was transferred to a polytetrafluoroethylene reactor and reacted at 180 °C for 22 h. After the reaction was completed, the mixture was cooled and washed multiple times with deionized water and anhydrous ethanol. The mixture was collected by centrifugation and finally dried to obtain the CoFe2O4 / ZnO-RGO composite material.

[0031] Example 6: The preparation of a ternary heterostructure electromagnetic wave absorbing material CoFe2O4 / ZnO-RGO was carried out according to the following steps: 2.0 g of sodium hydroxide (NaOH) was dissolved in 40 mL of ethylene glycol solution with a concentration of 1.0 mg / mL RGO. The solution was ultrasonically treated for 1 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Then, 1.0 g of zinc acetate (C4H6O4Zn·2H2O) was added to the solution and stirred for 1 h to form a suspension. Subsequently, 0.3 g of nano-CoFe2O4 particles were added and dispersed in the suspension. The solution was ultrasonically treated for 0.5 h at 25 °C using a CNC ultrasonic cleaner with a power of 150 W. Finally, the mixture was transferred to a polytetrafluoroethylene reactor and reacted at 180 °C for 24 h. After the reaction was completed, the mixture was cooled and washed multiple times with deionized water and anhydrous ethanol. The mixture was collected by centrifugation and finally dried to obtain the CoFe2O4 / ZnO-RGO composite material.

[0032] Test Example 1 The morphology of the CoFe2O4 / ZnO-RGO prepared in Example 3 above was characterized by transmission electron microscopy (TEM), such as... Figure 1 As shown in the figure, the rod-shaped material is ZnO, the single-layer wrinkled material is RGO, and the larger black nanoparticles can be clearly observed to be CoFe2O4 nanoparticles. Spherical CoFe2O4 nanoparticles and ZnO nanorods are loaded on the surface of graphene.

[0033] Test Example 2 The crystal form of the CoFe2O4 / ZnO-RGO prepared in Example 3 above was analyzed by X-ray diffraction (XRD) at a wavelength of λ = 1.54 Å and a scanning range of 10–80°. Figure 2It can be seen that, by comparing with the CoFe2O4 standard card (JCPDS22-1086), the diffraction peaks of 2θ at 18.3°, 30.1°, 35.3°, 43.1°, 57.2°, and 62.3° are consistent with the (111), (220), (311), (400), (511), and (440) crystal planes of CoFe2O4. Meanwhile, by comparing with the ZnO standard card... (JCPDS36-1451) found that the 2θ diffraction peaks at 31.8°, 34.4°, 36.3°, 47.5°, 56.6°, 62.9°, 66.4°, 67.9°, and 68.2° are consistent with the (100), (002), (101), (102), (110), (103), (200), (112), and (201) crystal planes of ZnO. Furthermore, the diffraction peak at 34.4° corresponding to the (002) crystal plane of ZnO has a significantly higher intensity than the other diffraction peaks, indicating that the ZnO crystal exhibits a distinct preferred orientation growth along the c-axis, which is consistent with its nanorod morphology. The absence of characteristic RGO diffraction peaks may be due to the strong diffraction of CoFe2O4, indicating that a pure-phase CoFe2O4 / ZnO-RGO ternary composite material was prepared.

[0034] Application Example 1: Study on Wave Absorption Performance The electromagnetic wave absorbing material prepared in Example 3 above was subjected to microwave absorption performance testing, including the following steps: (1) Testing electromagnetic parameters: The obtained product was ground and mixed with paraffin wax at a mass ratio of 1:1. It was pressed into a coaxial ring with an outer diameter of 7 mm, an inner diameter of 3 mm, and a thickness of 3 mm in a special mold. Its electromagnetic parameters were tested in the range of 2~18 GHz using a vector network analyzer. The real part of the permeability μ', the imaginary part of the permeability μ", the real part of the dielectric constant ε', and the imaginary part of the dielectric constant ε"; (2) Calculate the reflection loss value of the sample: According to the transmission line theory formula:

[0035]

[0036] The theoretically achievable reflection loss value is calculated, and the value obtained from the theoretical calculation reflects the wave absorption performance of the absorbing material. (3) Plot the frequency relationship between the complex permittivity and permeability of the sample in the frequency range of 2~18 GHz and the reflection loss diagram. Calculate the reflection loss value of the sample at different thicknesses according to the theory and compare the high-performance electromagnetic wave absorption value under ultra-thin thickness. The electromagnetic parameters of the CoFe2O4 / ZnO-RGO composite material were investigated in the frequency range of 2–18 GHz. The complex permittivity ε was among the electromagnetic parameters.r and complex permeability μ r and dielectric loss tangent tanδ ε and magnetic loss tangent tanδ μ Reflecting the absorption characteristics of electromagnetic waves, the real part of the complex permittivity (ε') and the real part of the complex permeability (μ') represent the ability to store electromagnetic energy, while the corresponding imaginary parts (ε" and μ") are related to energy dissipation. Figure 3 As can be seen, the ε' value shows a gradually decreasing trend, decreasing from 10.77 to 7.57, while the ε" value remains almost unchanged at around 2.5. Figure 4 As can be seen, both μ' and μ" values ​​show a slow decreasing trend, accompanied by some small fluctuations. The value of μ' gradually decreases from 1.13 to 0.96, and the value of μ" gradually decreases from 0.19 to 0.08. Figure 5 In the middle, the dielectric loss tangent is tanδ ε Between 0.23 and 0.31, the magnetic loss tangent is tanδ μ Between 0.07 and 0.18, it is clear that the CoFe2O4 / ZnO-RGO nanocomposite exhibits a high tanδ value across the entire test frequency range. ε Value greater than tanδ μ The value indicates that dielectric loss plays a dominant role. According to... Figure 6 The displayed 3D reflection loss diagram visually shows the wave absorption performance of the CoFe2O4 / ZnO-RGO nanocomposite material with different thicknesses of 0-10mm in the frequency range of 2-18GHz. Among them, the maximum reflection loss of the CoFe2O4 / ZnO-RGO nanocomposite material reaches -45.20dB at 5.18GHz when the thickness is 4.6mm. Figure 7The reflection loss values ​​of the CoFe2O4 / ZnO-RGO nanocomposite at thicknesses of 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 4.6 mm, and 5.0 mm are shown. It can be observed that the CoFe2O4 / ZnO-RGO nanocomposite exhibits excellent electromagnetic wave absorption performance at almost every thickness. This is attributed to the presence of magnetic particles (CoFe2O4) in the CoFe2O4 / ZnO-RGO nanocomposite, which provides magnetic loss; residual defects and functional groups in RGO, which lead to polarization relaxation and electronic dipole relaxation; and the addition of ZnO nanorods, which enhance spontaneous polarization, interfacial polarization, and impedance matching, thereby improving electromagnetic wave absorption performance. In summary, the excellent absorption performance stems from the synergistic effect of dielectric loss, conductive loss, and magnetic loss. The electromagnetic wave absorbing material prepared by this invention can effectively absorb electromagnetic waves, achieving high-performance electromagnetic wave absorption at various thicknesses, including thinner thicknesses. It is expected to construct a novel green and environmentally friendly electromagnetic wave absorbing composite material that combines lightweight, strong absorption, wide bandwidth, and good stability.

[0037] Comparative Example 1 1.35 g FeCl3·6H2O and 0.7 g CoCl2·6H2O were added to 40 mL of ethylene glycol and ultrasonically dispersed and mixed evenly. Then, 1.8 g sodium acetate and 0.5 g polyethylene glycol were added and ultrasonically dissolved again. The mixture was then transferred to a round-bottom flask and stirred at 50 °C for 1 h. After stirring, the mixture was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 200 °C for 8 h. After cooling to room temperature, the mixture was separated by magnetic precipitation, washed three times with deionized water and anhydrous ethanol, and dried to obtain CoFe2O4 nanoparticles.

[0038] The microwave absorption performance of the material was tested according to the implementation method of Application Example 1. Since it is only a single magnetic medium material, it exhibits disadvantages such as strong attenuation capability, poor impedance matching, high density, aggregation and large coating thickness, which cannot meet the requirements of broadband and lightweight.

[0039] Comparative Example 2 1.35 g FeCl3·6H2O and 0.7 g CoCl2·6H2O were added to 40 mL of ethylene glycol and ultrasonically dispersed and mixed evenly. Then, 1.8 g sodium acetate and 0.5 g polyethylene glycol were added and ultrasonically dissolved again. The mixture was then transferred to a round-bottom flask and stirred at 50 °C for 1 h. After stirring, the mixture was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 200 °C for 8 h. After cooling to room temperature, the mixture was separated by magnetic precipitation, washed three times with deionized water and anhydrous ethanol, and dried to obtain CoFe2O4 nanoparticles. Subsequently, 0.1 g of the prepared CoFe2O4 nanoparticle powder was weighed and dispersed in 100 mL of anhydrous ethanol solution containing 0.68 g of Zn(Ac)2·2H2O. After ultrasonic stirring and mixing, the mixture was transferred to a three-necked round-bottom flask. The flask was then placed in a water bath at 60 °C for mechanical stirring. At the same time, 25 mL of anhydrous ethanol solution containing 0.25 g of NaOH was added dropwise to the three-necked round-bottom flask using a separatory funnel. After the addition was completed, stirring was continued for 4 h. Finally, the product was collected by magnet, washed several times with anhydrous ethanol, and dried to obtain core-shell structured CoFe2O4@ZnO nanoparticles.

[0040] The electromagnetic wave absorption performance of the material was tested according to the implementation method of Application Example 1. It did not show a good electromagnetic wave absorption effect. This can be attributed to the improper thickness of the ZnO shell, which caused the electromagnetic parameters of the material to fail to meet the impedance matching and maximum loss, thus failing to effectively absorb electromagnetic waves.

[0041] Comparative Example 3 140 mg of graphene oxide (GO) and 140 mg of sodium dodecylbenzenesulfonate (SDBS) were weighed and dispersed in 140 mL of deionized water. The dispersion was carried out under ultrasonic treatment for 0.5 h, and then transferred to a three-necked flask. Next, 0.5 mL of 80 wt% hydrazine hydrate (N2H4·H2O) was slowly added, and the mixture was stirred in a water bath at 80 °C for 24 h. After the reaction was completed, the resulting mixture was cooled to room temperature, filtered, and washed three times each with deionized water and ethanol. The purified product was then immersed in an ethylene glycol solution to obtain an ethylene glycol solution of RGO. 40 mL of the 1 mg / mL RGO aqueous solution prepared above was then ultrasonically dispersed for 30 minutes. Ferric chloride hexahydrate (FeCl3·6H2O) and cobalt chloride hexahydrate (CoCl2·6H2O) were added, and the mixture was ultrasonically dispersed and mixed thoroughly. 1.0 g of sodium acetate (NaAc) and 1.0 g of polyethylene glycol (PEG) were added, and the mixture was further ultrasonically dissolved. The mixture was then transferred to a round-bottom flask, stirred at 50 °C for 1 h, and then transferred to a 100 mL polytetrafluoroethylene reactor. The reactor was reacted at 200 °C for 8 h, cooled to room temperature, and separated by magnetic precipitation. The mixture was washed three times with deionized water and anhydrous ethanol, and dried to obtain the CoFe2O4-RGO composite material. 0.68 g of Zn(Ac)2·2H2O and an appropriate amount of the CoFe2O4-RGO nanocomposite prepared above were weighed and placed in a 100 mL... After being ultrasonically stirred and mixed evenly in mL of anhydrous ethanol solution, the mixture was transferred to a three-necked round-bottom flask and mechanically stirred in a 60 ℃ water bath for 4 h. While stirring, 25 mL of anhydrous ethanol solution containing 0.25 g NaOH was added dropwise. After the reaction was completed, the prepared sample was separated by a magnet, washed several times with anhydrous ethanol, and then placed in a vacuum oven for drying. After grinding, the CoFe2O4@ZnO-RGO composite material was obtained.

[0042] The absorption performance of the material was tested according to the implementation method of Application Example 1 (Table 1). Although it had a good minimum reflection loss value, the impedance matching was poor and it failed to meet the requirements of "thin", "light", "wide" and "strong" electromagnetic wave absorbing materials.

[0043] The specific embodiments of the present invention have been described in detail above. It should be noted that the present invention is not limited to the specific embodiments described above. Various modifications or alterations can be made by those skilled in the art without departing from the scope of protection defined by the claims, and all such modifications or alterations fall within the scope of the present invention.

Claims

1. A ternary heterostructure CoFe2O4 / ZnO-RGO nanocomposite electromagnetic wave absorbing material, characterized in that, The microwave absorbing material includes CoFe2O4, ZnO, and reduced graphene oxide (RGO). Spherical CoFe2O4 nanoparticles and ZnO nanorods together form a heterostructure, which is loaded on the surface of sheet-like reduced graphene oxide.

2. The absorbent material according to claim 1, characterized in that, Reduced graphene oxide exists as a single layer of wrinkled structures.

3. The absorbent material according to claim 1, characterized in that, The mass percentages of CoFe2O4, ZnO, and reduced graphene oxide are 8.9%~22.4%, 74.6%~89.3%, and 1.7%~3.3%, respectively.

4. The method for preparing the absorbent material according to any one of claims 1-3, characterized in that, Includes the following steps: Step 1: Disperse reduced graphene oxide in ethylene glycol to obtain an RGO solution, then add sodium hydroxide, sonicate until completely dissolved, add zinc acetate, stir until homogeneous, and obtain a suspension; Step 2: Then add spherical CoFe2O4 nanoparticles, sonicate, heat to react, cool after the reaction is complete, wash repeatedly with deionized water and anhydrous ethanol, centrifuge, and dry to constant weight to obtain the absorbent material.

5. The method according to claim 4, characterized in that, The preparation method of RGO is as follows: 140 mg of graphite oxide (GO) and 140 mg of sodium dodecylbenzenesulfonate (SDBS) were dispersed in 140 mL of deionized water, and 0.5 mL of 80 wt% hydrazine hydrate was added. The reaction was carried out in a water bath at 80 °C for 24 h. After the reaction was completed, the RGO was collected and washed by vacuum filtration.

6. The method according to claim 4, characterized in that, CoFe2O4 nanoparticles were prepared by the following method: 1.35 g FeCl3·6H2O and 0.7 g CoCl2·6H2O were added to 40 mL of ethylene glycol and ultrasonically dispersed and mixed evenly. Then, 1.8 g sodium acetate and 0.5 g polyethylene glycol were added and ultrasonically dissolved again. After stirring at 50 °C for 1 h, the mixture was transferred to a 100 mL polytetrafluoroethylene reactor and reacted at 200 °C for 8 h. After cooling to room temperature, the mixture was separated by magnetic precipitation, washed with deionized water and anhydrous ethanol, and dried to obtain CoFe2O4 nanoparticles.

7. The method according to claim 4, characterized in that, The mass ratio of NaOH to RGO solution volume is (1.0~2.0) g : (20~40) mL, the concentration of RGO solution is 1.0 mg / mL, and the mass ratio of NaOH to zinc acetate is (1.0~2.0) : (0.5~1.5).

8. The method according to claim 4, characterized in that, The mass ratio of NaOH to spherical CoFe2O4 nanoparticles is (1.0~2.0):(0.5~1.5).

9. The method according to claim 4, characterized in that, The reaction is carried out under heating conditions of 120 ℃ to 180 ℃.

10. An absorbing material according to any one of claims 1-3 for electromagnetic wave absorption.

Citation Information

Patent Citations

  • A polyhydroxyazo-grafted graphene oxide-based material and its application in electromagnetic wave absorption.

    CN119822363B

  • Carbonyl iron powder-graphite electromagnetic wave absorption composite material and preparation and application thereof

    CN120248829A

Cited By

  • A method for preparing a band-tunable CoFe@C / ZnO coral-structured lightweight microwave absorbing material

    CN122302821A